Shoots and leaves: exploring the impacts and fragile sustainability of sustainable place-making projects working with marginalised people. (1st July 2020) - Ramsden, Sam
Abstract : This article contributes to emerging research on sustainable place-making, but makes an important contribution through a strong focus on outcomes for marginalised people and the need for long-term sustainability. Sustainable place-making combines 'place-making' and 'sustainable development' to describe locally focused action working towards social, economic and environmental goals (Franklin and Marsden, 2015). The article explores an externally funded charity-led project working in a deprived area of the UK, implementing urban agriculture, community gardening and household energy activities. The project successfully engaged marginalised people, who strongly voiced outcomes including reduced isolation, improved mental health and increased resilience and self-reliance. Support from staff, volunteering in a team, enjoying gardening, accessing nature and financial savings provided a platform for impacts. Environmental outcomes were less tangible but included improvements to the local environment and reduced energy usage. However, after the funding finished, marginalised participants were vulnerable to outcomes not being sustained in the long term.